Listeria monocytogenes Occurrence and Adherence to Recommendations: small and Large Retail Delicatessens in Iowa - Pierquet, Jennifer; Susan, W. Arendt; Rahamat, Syafiqah; Hall, Nancy; Mandernach, Steven; Reeb, Valerie; Speltz, Mark (International Association for Food Protection, 2020)
The goal of this research was to determine the prevalence of Listeria monocytogenes in Iowa retail delicatessens and assess environmental aspects that mitigate L. monocytogenes. Fifty-seven small and large retail delicatessens in Iowa were selected randomly. More small operations (n = 43) were included as compared with larger stores, given the higher frequency of violations. An environmental assessment instrument was used to determine environmental factors and practices. At least five microbial samples were collected per site. We collected 286 (74.3%) of 385 microbial samples from small deli operations and 99 (25.7%) of 385 samples from large deli operations. Samples were taken from various zone 1 and 2 areas, such as the slicer, deli case, and meat scale; three (0.08%) samples were positive for L. monocytogenes. Regarding environmental aspects, not preparing, holding or storing ready-to-eat products near raw products (n = 30, 53%) was practiced by the fewest delis. The majority of establishments were observed covering, wrapping, or protecting ready-to-eat products when not in use to prevent contamination (n = 56, 98.2%). Comparisons were made to the U.S. Department of Agriculture Food Safety and Inspection Service Guidance on environmental practices, and 60% of the operations surveyed were in adherence with at least seven of the eight recommendations.